PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP SMOOTHNESS PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE - Vania Allan Sutanto; Juniarti Juniarti (Business Accounting Review, 2016)
The purpose of this research was to find out how Corporate Social Responsibility (CSR) affected toward earning smoothness in a company. Corporate Social Responsibility variable measured by using Global Reporting Initiative (GRI) Index 3.1. Earning quality variable measured by using smoothness. The control variables in this research were firm size and leverage. This research was conducted on the public company in the property and real estate sector listed in Indonesia Stock Exchange and had annual report from 2010-2014 with total sample of 104 observation. This research proved that there was positive relationship between CSR and smoothness. This research also proved that there was negative relationship between leverage and smoothness. On the other hand, this research had not succeeded in finding out the influence between firm size with smoothness.